The Impact of Interface Design During an Initial High-Technology AAC Experience: A Collective Case Study of People with Aphasia. (December 2014) - Dietz, Aimee; Weissling, Kristy; Griffith, Julie; McKelvey, Miechelle; Macke, Devan
Abstract The purpose of this collective case study was to describe the communication behaviors of five people with chronic aphasia when they retold personal narratives to an unfamiliar communication partner using four variants of a visual scene display (VSD) interface. The results revealed that spoken language comprised roughly 70% of expressive modality units; variable patterns of use for other modalities emerged. Although inconsistent across participants, several people with aphasia experienced no trouble sources during the retells using VSDs with personally relevant photographs and text boxes. Overall, participants perceived the personally relevant photographs and the text as helpful during the retells. These patterns may serve as a springboard for future experimental investigations regarding how interface design influences the communicative and linguistic performance of people with aphasia.